Effects of deletion of mutant huntingtin in steroidogenic factor 1 neurons on the psychiatric and metabolic phenotype in the BACHD mouse model of Huntington disease. - Barbara Baldo; Rachel Y Cheong; Åsa Petersén (PLoS ONE)
Psychiatric and metabolic features appear several years before motor disturbances in the neurodegenerative Huntington's disease (HD), caused by an expanded CAG repeat in the huntingtin (HTT) gene. Although the mechanisms leading to these aspects are unknown, dysfunction in the hypothalamus, a brain region controlling emotion and metabolism, has been suggested. A direct link between the expression of the disease causing protein, huntingtin (HTT), in the hypothalamus and the development of metabolic and psychiatric-like features have been shown in the BACHD mouse model of HD. However, precisely which circuitry in the hypothalamus is critical for these features is not known. We hypothesized that expression of mutant HTT in the ventromedial hypothalamus, an area involved in the regulation of metabolism and emotion would be important for the development of these non-motor aspects. Therefore, we inactivated mutant HTT in a specific neuronal population of the ventromedial hypothalamus expressing the transcription factor steroidogenic factor 1 (SF1) in the BACHD mouse using cross-breeding based on a Cre-loxP system. Effects on anxiety-like behavior were assessed using the elevated plus maze and novelty-induced suppressed feeding test. Depressive-like behavior was assessed using the Porsolt forced swim test. Effects on the metabolic phenotype were analyzed using measurements of body weight and body fat, as well as serum insulin and leptin levels. Interestingly, the inactivation of mutant HTT in SF1-expressing neurons exerted a partial positive effect on the depressive-like behavior in female BACHD mice at 4 months of age. In this cohort of mice, no anxiety-like behavior was detected. The deletion of mutant HTT in SF1 neurons did not have any effect on the development of metabolic features in BACHD mice. Taken together, our results indicate that mutant HTT regulates metabolic networks by affecting hypothalamic circuitries that do not involve the SF1 neurons of the ventromedial hypothalamus.